29.6k views
8 votes
Which shows the expressionbelow simplified. (8×10‐⁴)×0.08

User Also
by
4.9k points

1 Answer

10 votes

Answer:


(8 * 10^(-4)) * 0.08 =
64 * 10^(-6) =
(64)/(10^6) =
(64)/(1000000) =
0.000064

Explanation:

Given


(8 * 10^(-4)) * 0.08

Required

Simplify


(8 * 10^(-4)) * 0.08

Express 0.08 as standard form


(8 * 10^(-4)) * 8 * 10^(-2)

Remove bracket


8 * 10^(-4) * 8 * 10^(-2)

Apply commutative property:


8* 8 * 10^(-4) * 10^(-2)


64 * 10^(-4) * 10^(-2)

Apply law of indices


64 * 10^(-4-2)


64 * 10^(-6)

Solving further: Express
10^(-6) as fraction by applying law of indices


64 * (1)/(10^6)


(64)/(10^6)


10^6 = 1000000

So, we have:


(64)/(1000000)

Lastly:


0.000064

Hence:


(8 * 10^(-4)) * 0.08 =
64 * 10^(-6) =
(64)/(10^6) =
(64)/(1000000) =
0.000064

User Sofiane Majdoub
by
5.3k points